PENGARUH TOTAL ASSET TURNOVER (TATO), DEBT TO EQUITY RATIO (DER) DAN RETURN ON INVESTMENT (ROI) TERHADAP HARGA SAHAM PADA PT. HM. SAMPOERNA. Tbk DI BURSA EFEK INDONESIA PERIODE 2006 – 2014 - Atikah Atikah; Yunan Surono (Eksis: Jurnal Ilmiah Ekonomi dan Bisnis, 2015)
The purpose of the Company is Prosperity Maximizing Shareholder Or Maximize the Value of the Company. If the Company is Providing Value Investing Now Bigger From Investing, So Will Increase Corporate Value. Total Asset Turnover "Is Used To Measure Ratio Turnover All Assets Owned Companies And Measure How Many Sales Provided by Each Rupiah Assets. Debt To Equity Ratio, Ratio Is Used To Know Comparison Between Total Debt With Equity .Return On Investment (ROI), marupakan Ratio Yang Showing Results Over Total Assets Used in Companies. Stock Price Closing Price Is Stock Market Observation Period For Each and Every type yanng Stock cite Samples And Movements Observed borne by investors. In Silmutran entire Significant Against Influential Variables Variable Bound, That F Amounting 5.113 0.043 With Significant Value While It's F count < F Table Namely 5.113 < 8.9406 and 0.043 Significant value > 0.50. Meaning Means are Strong Influence Variable Total Asset Turnover, Debt To Equity and Return On Investment Simultaneous Share Price. Partial Variable TATO has no effect, Due In Predicting Stock Price For Above Of The significant value of 0.05 (0.311 > 0.05). Variable DER No Effect In Predicting Stock Price For Above Of The significant value of 0.05 (0.108 > 0.05.). Variable ROI Influential In Predicting Stock Price, Due From Under The significant value of 0.05 (0.042 > 0.05).Keyword: total asset turnover, debt to equity ratio, return on investment The purpose of the Company is Prosperity Maximizing Shareholder Or Maximize the Value of the Company. If the Company is Providing Value Investing Now Bigger From Investing, So Will Increase Corporate Value. Total Asset Turnover "Is Used To Measure Ratio Turnover All Assets Owned Companies And Measure How Many Sales Provided by Each Rupiah Assets. Debt To Equity Ratio, Ratio Is Used To Know Comparison Between Total Debt With Equity .Return On Investment (ROI), marupakan Ratio Yang Showing Results Over Total Assets Used in Companies. Stock Price Closing Price Is Stock Market Observation Period For Each and Every type yanng Stock cite Samples And Movements Observed borne by investors. In Silmutran entire Significant Against Influential Variables Variable Bound, That F Amounting 5.113 0.043 With Significant Value While It's F count < F Table Namely 5.113 < 8.9406 and 0.043 Significant value > 0.50. Meaning Means are Strong Influence Variable Total Asset Turnover, Debt To Equity and Return On Investment Simultaneous Share Price. Partial Variable TATO has no effect, Due In Predicting Stock Price For Above Of The significant value of 0.05 (0.311 > 0.05). Variable DER No Effect In Predicting Stock Price For Above Of The significant value of 0.05 (0.108 > 0.05.). Variable ROI Influential In Predicting Stock Price, Due From Under The significant value of 0.05 (0.042 > 0.05).Keyword: total asset turnover, debt to equity ratio, return on investment